EFEKTIVITAS TENDANGAN YANG DIGUNAKAN DALAM PERTANDINGAN KEJUARAAN PENCAK SILAT - Ivan Pranata Hadi Kusuma; Edi Purnomo; Eka Supriatna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of the study was to determine the effectiveness of the kicks used in the pencaksilat championship match. Quantitative descriptive research, using survey method. Theresearch instrument uses a match analysis table format about the number of incomingkicks on the target. The research sample consisted of 60 athletes using the SampleRandom Sampling technique. The data analysis technique used a descriptive percentageformula. The results of the study on the effectiveness of kicks in PORPROV, POPNAS,and ASIAN GAMES matches. The effectiveness of the T kick was more on target with thepercentage (49.43%) PORPROV, (41.74%) POPNAS, and (48.24%) ASIAN GAMES.Meanwhile, in the PRAPON, PON, SEA GAMES championships. The effectiveness ofside kicks is more on target with the percentage (41.76%) PRAPON, (48.33%) PON, and(50%) SEA GAMES. And if the overall championship results are combined. (1) Frontkick 187 times with a percentage of 31.80%. (2) Side kicks 169 times with a percentageof 28.74%. (3) Kick T 229 times with a percentage of 38.94%. (4) Back kicks 3 times witha percentage of 0.51%. These results show that the effectiveness of the T-kick hit thetarget a lot with a percentage of (38.94%).Keywords: Effectiveness, Kick, Pencak Silat, Championship Match.